2015
DOI: 10.1186/s13071-015-0684-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, species identification and genotyping Cryptosporidium from livestock and deer in a catchment in the Cairngorms with a history of a contaminated public water supply

Abstract: BackgroundThe apicomplexan parasite Cryptosporidium represents a threat to water quality and public health. An important zoonotic species involved in human cryptosporidiosis from contaminated water is Cryptosporidium parvum (C. parvum), the main reservoirs of which are known to be farm livestock particularly neonatal calves, although adult cattle, sheep, lambs and wildlife are also known to contribute to catchment loading of C. parvum. This study aimed to establish Cryptosporidium prevalence, species and genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
75
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 33 publications
13
75
2
Order By: Relevance
“…In addition to sanitary sewage, contamination of supply sources by cattle feces is a constant concern, since these animals are reservoirs of the zoonotic genotypes of Cryptosporidium spp. and Giardia spp.. Additionally, they are responsible for environmental contamination, because they eliminate a large amount of oocysts in feces, with bovine cattle increasing the possibility of outbreaks in humans (MARTINS-VIEIRA et al, 2009;WELLS et al, 2015).…”
Section: Water Pathogensmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to sanitary sewage, contamination of supply sources by cattle feces is a constant concern, since these animals are reservoirs of the zoonotic genotypes of Cryptosporidium spp. and Giardia spp.. Additionally, they are responsible for environmental contamination, because they eliminate a large amount of oocysts in feces, with bovine cattle increasing the possibility of outbreaks in humans (MARTINS-VIEIRA et al, 2009;WELLS et al, 2015).…”
Section: Water Pathogensmentioning
confidence: 99%
“…Despite the low prevalence of C. parvum in steers and adults, some studies have identified this species in this age group (FAYER et al, 2007;BUDU-AMOAKO et al, 2012;WELLS et al, 2015). In Brazil, C. parvum was also more frequently identified in calves up to 2 months of age (THOMAZ et al, 2007;MEIRELES et al, 2011;COUTO et al, 2014).…”
Section: Epidemiological Aspects Of Bovine Cryptosporidiosismentioning
confidence: 99%
See 3 more Smart Citations